Gyogamdan, a Traditional Medicine Prescription, Ameliorated Dermal Inflammation and Hyperactive Behavior in an Atopic Dermatitis Mouse Model Exposed to Psychological Stress. (31st March 2021) - Nguyen, Ly Thi Huong; Nguyen, Uy Thai; Choi, Min-Jin; Oh, Tae-Woo; Yang, In-Jun; Shin, Heung-Mook
Abstract : Psychological stress (PS) plays a significant role as an aggravating factor in atopic dermatitis (AD). The traditional medicine prescription, Gyogamdan, has been used to treat chest discomfort and mood disorders caused by PS. This study investigated the effects of an ethanolic extract of Gyogamdan (GGDE) on stress-associated AD models and the underlying mechanisms. 2, 4-Dinitrochlorobenzene- (DNCB-) treated BALB/c mice were exposed to social isolation (SI) stress. The effects of orally administered GGDE (100 or 500 mg/kg) were evaluated by ELISA, western blotting, and an open field test (OFT). SI stress exaggerated the skin inflammation and induced locomotor hyperactivity in the AD mouse model. GGDE reduced the levels of IgE, TNF- α, IL-13, eotaxin, and VEGF and mast cell/eosinophil infiltration and prevented the decreases in the levels of involucrin and loricrin in the skin. GGDE also suppressed the SI-induced increases in corticotropin-releasing hormone (CRH), adrenocorticotropic hormone (ACTH), and corticosterone (CORT) in socially isolated AD mice. Furthermore, GGDE reduced traveling distances and mean speed significantly in the OFT. The in vitro experiments were performed using HaCaT, HMC-1, PC12, and BV2 cells. In the TNF- α /IFN- γ - (TI-) stimulated HaCaT cells, GGDE decreased the thymus and activation-regulated chemokine (TARC) and macrophage-derived chemokine (MDC) production significantly by inhibiting p-STAT1 and NF- κ B signaling. GGDE also reduced VEGF production in HMC-1 cells stimulated with CRH/substance P (SP) by inhibiting p-ERK signaling pathway. GGDE increased the cell viability significantly and suppressed apoptosis in CORT-stimulated PC12 cells. Moreover, GGDE suppressed the LPS-induced production of NO, TNF- α, IL-1 β, and IL-6 in BV2 cells. These results suggest that GGDE might be useful in patients with AD, which is exacerbated by PS.